Makna “Mengikat” Bahasa Bali: Pendekatan Metabahasa Semantik Alami - I Nengah Sudipa (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The Balinese verb ngiket ‘to tie’ can be expressed by a number of lexicons, namely: ngiket/negul, nalinin, pesel, ngimpus, nyangkling, ngeju, nyamok, nyeet, medbed/maste, nyangcang, ngantus, ngancét, and nyepingin. Through Natural Semantic Metalanguage (NSM) approach, it can reveal that the first three Balinese lexicons have slight differences although they are belonging to the similar semantic field, the rest, however carry the overt semantic differences. Ngiket/negul, nalinin and mesel seem to have similar object as well as the instruments used to do the activity, that is tali ‘string, rope, thread, etc’. The others, such as ngimpus, for instance has specific object, that is the legs of animal or human being to be tied, while nyangkling referred to the hands.